Penerapan Metode Kisah Dalam Pembelajaran Pendidikan Agama Islam di Kelas V SDN 01 Koto Rajo Kabupaten Pasaman - Misdalipah Misdalipah; Fauzan Fauzan (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This research is entitled "Application of the Story Method in Learning Islamic Religious Education at SDN 01 Koto Rajo, Pasaman Regency" which was compiled by Misdalipah Nim 2119212. The background of the author of this thesis is because there are several problems that occur in class V at SDN 01 Koto Rajo, Pasaman Regency. Among them the teacher has applied or used the story method about the story of the prophet such as the journey of the prophet's life, but there is still a lack of knowledge or understanding of students regarding the stories of the prophet in learning Islamic religious education and the focus of students in learning is ongoing as evidenced by many students who scramble, walk and talk to friends. The researcher aims to find out how the teacher applies the story method in class V SDN 01 Koto Rajo. This research uses a qualitative descriptive research approach. Qualitative descriptive is a research procedure that produces descriptive data in the form of written words from observed behavior. while the data collection techniques that the authors use are observation, interviews and documentation. The key informants in this study were the principal and homeroom teacher, the main informant was the PAI subject teacher and fifth grade students. The results of this study proved that Islamic religious education subject teachers applied the story method in class V in accordance with the story method, namely the first, the teacher sets goals, prepares props, determines the topic of the story, arranges the story outline and develops the story framework, composes the story text, pays attention to sitting position, uses language that is easy to understand and pays attention to voice intonation, conveys the values contained, asks questions and gives story transcript. secondly, the obstacles faced by teachers in applying the story method in learning Islamic religious education are due to the lack of teaching aids, difficulties in packing material, and the lazy character of students. It can be concluded that Islamic religious education subject teachers apply the story method with the steps of the story method, where through this application it is hoped that Islamic religious education teachers in grade V will further improve the application of the story method and the school principal pays more attention to learning media as teaching aids that can refers to more effective and efficient learning.